Managing the ASEAN Economic Integration Process in the Philippines: An Assessment of Progress in Trade Liberalization and Facilitation - Erlinda M. Medalla (Philippine Institute for Development Studies (PIDS), 2012)
This paper is part of the Philippine study for the ERIA project on the Mid-Term Review (MTR) of the ASEAN Economic Community (AEC) Blueprint. A milestone in ASEAN economic cooperation is the Cebu Declaration on the Acceleration of the Establishment of an ASEAN Community by 2015 during the 12th ASEAN summit in 2007, and subsequently the passing of the ASEAN Charter. A midterm review of where the member countries are in moving toward the AEC is thus timely. At the core of ASEAN integration is free flow of trade in goods. An essential part of the midterm review is an assessment of progress in the area of trade liberalization and facilitation. Toward this end two sets of surveys are undertaken by the study: (1) an MTR Questionnaire for Government Officials, and (2) Firm MTR Survey on Import/Export and Customs Clearance. The questionnaire for government officials aims to gather information on aspects of ASEAN customs development and integration and the implementation of the National Single Window (NSW) and ASEAN Single Window. The survey of firms will provide the view from users by getting their experience on customs clearance and permit release process in other government agencies. Recommendations of the ways forward are then suggested.
Keywords: 330; trade liberalization; economic integration; ASEAN; Philippines; trade facilitation; national single window; ASEAN single window (ASW)